Evaluación de medios filtrantes en un biofiltro percolador de flujo continúo a escala de laboratorio (2010)
This study was developed in order to analyse the incidence of filter media in the Process of nitrogen and phosphorus removal present in water collected from a natural Source. A four stage biofilter anaerobic, aerobic, anoxic and aerobic was used. It was Posible evaluate two different kinds of filter media, scourer and PVC. The selection of the filter media was based on the low cost and low conventionality. It was analyzed the nitrate and phosphate concentration from the inlet and outlet wáter and the Quantity of colony formation units adhered to the filter media in the anaerobic stage. It was determined that the scourer offered most biofilm stability for the support of the Bacterial biofilm and therefore for a better biofilter performance.